A novel fluorescent turn-on probe for imaging biothiols based on SNAr substitution-skeletal rearrangement strategy. Issue 3 (8th January 2019) - Ren, Aishan; Zhu, Dongjian; Zhong, Xing; Xiong, Yuhao; Duan, Zhenhua
Abstract : 2 is a novel fluorescent turn-on probe for imaging biothiols based on SN Ar substitution-skeletal rearrangement strategy with dramatic fluorescence enhancement and high sensitivity. Abstract : A novel fluorescent turn-on probe2 not only exhibited dramatic fluorescence enhancement by quinoline-to-quinolinone transformation, but also showed high sensitivity in the order Cys > GSH > Hcy. Importantly, 2 was successfully applied for imaging of biothiols in living cells.